2013
DOI: 10.1111/jmcb.12052
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Policy and Sovereign Bond Spreads in Developing Countries

Abstract: This paper empirically analyzes how exchange rate policy a¤ects the issuance and pricing of international bonds for developing countries. We …nd that countries with less ‡exible exchange rate regimes pay higher sovereign bond spreads and are less likely to issue bonds. Quantitatively, changing a free- ‡oating regime to a …xed regime decreases the likelihood of bond issuance by 4.6% and increases the bond spread by 1.3% on average. Furthermore, countries with real exchange rate overvaluation have higher bond sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The second column in Table 4 and 5 summarizes moments of data. 26 Output data are As is obvious in Table 5, the model matches business cycle statistics in data in both pre-default and post-default periods. Our model replicates volatile consumption and trade balance/GDP volatility, both of which are prominent features of emerging economy business cycle models as in Aguilar and 2 6 See also Arellano (2008) and Yue (2010) for similar treatment of simulation.…”
Section: Simulation -Argentinamentioning
confidence: 92%
See 1 more Smart Citation
“…The second column in Table 4 and 5 summarizes moments of data. 26 Output data are As is obvious in Table 5, the model matches business cycle statistics in data in both pre-default and post-default periods. Our model replicates volatile consumption and trade balance/GDP volatility, both of which are prominent features of emerging economy business cycle models as in Aguilar and 2 6 See also Arellano (2008) and Yue (2010) for similar treatment of simulation.…”
Section: Simulation -Argentinamentioning
confidence: 92%
“…In a standard model with a risk-neutral creditor, bond spreads do not include any spread premia since bond prices are simply determined by default probability. On the contrary, in the current model with the riskaverse creditor, bond prices are determined by interaction between stochastic discount factors and expected payo¤, as shown in equation (25) and (26). Risk premia, due to risk aversion of the creditor, are included in bond spreads and increase spreads close to the data.…”
Section: Comparison With the Model Of A Risk-neutral Creditormentioning
confidence: 99%
“…Cheaper exchange rates serve as a subsidy to exporters and a duty to importers [27] and countries with a strict or less flexible exchange rate regime are less likely to sell bonds [29]. Lower inflation often increases currency values but the issue is complicated by the fact that central banks exert influence over both inflation and exchange rates through monetary policy.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Focusing on developing countries, Jahjah, Wei and Yue (2013) showed that exchange rate policy affects the issuance and pricing of sovereign bonds, while Correa et al . (2014) examined the relations among support to banks, stock returns and sovereign credit ratings. …”
mentioning
confidence: 99%